The Potential Application Of Switchable Matched Parallel-Coupled Stub Resonator In SPDT Discrete Switch Design - Shairi, Noor Azwan; Ahmad, Badrul Hisham; Peng Wen, Wong (2012)
This paper discusses the potential application of switchable matched parallel-coupled stub resonator for isolation improvement of Single Pole Double Throw (SPDT) discrete switch in wireless communication system. In addition, an absorptive SPDT switch also can be obtained by the use of the matched resonator. Frequency spectrum at 2.010-2.025 GHz band for TD-SCDMA is chosen to demonstrate this technique. The discussion of the conceptual and operation of the matched resonator and the SPDT switch are included in this paper. The circuit is simulated for further analysis in simulation software where parameters of microstrip line and FR4 substrate are taken into account. Result in simulation shows 15 dB return loss at absorptive port with 40 dB isolation at resonant frequency and more than 30 dB of isolation between 2.010-2.025 GHz.